Differentiated Instruction in Teaching Writing Narrative Text to Students of SMA 2 Tegal - Setyorini, Dwi; Wahyuni, Sri; Fitriati, Sri Wuli (Cakrawala: Jurnal Pendidikan, 2025)
Teaching writing requires teachers to use an appropriate approach. Differentiated instruction can be applied as it can facilitate children's diverse learning needs as well as one of the embodiments of the emancipated curriculum. This mixed-method research explored the implementation of differentiated instruction in teaching English as a foreign language and focuses on writing narrative text to high school students. The main objective of this study is to explain the teacher’s preparation, implementation, and its effects. A teacher and a class of students participated in this study. The result shows that the teacher has an understanding and concept of the application of DI in the classroom. The teacher implemented content, process, and product differentiation based on the students’ readiness level and interest. DI was proven to have positive impacts on students. The research implications are expected to guide practitioners, policymakers, and other stakeholders in applying research findings in practical settings.